PEMBUATAN APLIKASI KOMPRESI FILE WAVE DENGAN METODE ALGORITMA HUFFMAN MENGGUNAKAN VISUAL BASIC - Muhammad Syah; Naniek Widyastuti; Muhammad Sholeh (Jurnal SCRIPT, 2015)
In the Windows operating system a sound file format is widely used wave format (*, WAV). Wave format is widely used for purposes such as gaming and multimedia. The format of this wave is actually a kind of rough format (raw format) in which the voice signal directly recorded and quantized into digital data. In this program will be made specifically to the compression and decompression of audio files of type wave and have manifold PCM audio formats (Pulse Code Modulation) and supports a maximum of 2 pieces of the channel channel (mono and stereo). The percentage of file compression wave does not depend on the size of the file but rather rely on the frequency of the wave file. The more repetition of data contained in the file data chunk wave then the lower the compression ratio.